Можливості розвитку урботуризму в місті Лозова та проблеми в зв'язку з військовою агресією росії - Гайдай, Сергій Вікторович; Черченко, О. А. (Київський національний університет імені Тараса Шевченка, 2025)
У статті досліджено потенціал розвитку урботуризму в місті Лозова в умовах післявоєнної реконструкції. Розкрито роль урбаністичного туризму як інструменту соціальної реінтеграції, економічного пожвавлення та відновлення локальної ідентичності українських міст, що постраждали від російської агресії. Проаналізовано історико-культурні, індустріальні, транспортні та соціальні ресурси Лозової, визначено вплив воєнних руйнувань на їх туристичну привабливість. Окреслено перспективні напрями розвитку міського туризму, включно з індустріальними, культурними, гастрономічними та екологічними ініціативами. Запропоновано поетапну модель післявоєнного відновлення туристичної сфери, що включає коротко-, середньо- та довгострокові заходи для формування конкурентоспроможної туристичної дестинації. Результати дослідження підкреслюють, що комплексний підхід до розвитку урботуризму може стати ключовим чинником відбудови міста, активізації громади та формування позитивного іміджу Лозової у післявоєнний період.

The article explores the potential for developing urban tourism in the city of Lozova in the context of post-war reconstruction and the restoration of the urban environment. It highlights the importance of urban tourism as a modern tool for social reintegration, economic revitalization, and the strengthening of local identity in Ukrainian cities affected by Russian aggression. Special attention is given to the analysis of Lozova’s historical, cultural, industrial, transport, and social resources, which, despite wartime losses, retain significant potential for forming an attractive tourist offer. The extent of damage to the city’s infrastructure and its impact on the perception of the city by tourists and investors is also assessed. The paper identifies promising directions for urban tourism development, including industrial tours, cultural and artistic events, gastronomic routes, as well as ecological and recreational initiatives. The importance of integrating modern urban approaches, encouraging community participation, and fostering partnerships with local businesses is emphasized. A step-by-step model for the post-war recovery of the tourism sector is proposed, covering short- , medium-, and long-term measures aimed at creating a competitive and recognizable destination. The results of the study demonstrate that the comprehensive development of urban tourism can become a key factor in Lozova’s recovery, stimulate civic engagement, support the formation of a positive city image, and attract new opportunities in the post-war period.
Possibilities for the development of urban tourism in the city of Lozova and challenges caused by russia’s military aggression
Keywords: урботуризм; післявоєнне відновлення; туристичний потенціал; індустріальна спадщина; урбаністичний простір; urban tourism; post-war recovery; tourism potential; industrial heritage; urban space